IDENTIFICATION OF SOIL CORROSION POTENTIAL FOR PLANNING IN THE GAS PIPELINE CATHODIC PROTECTION SYSTEM - Agus Solehudin; Enda Permana; Haipan Salam (Spektra: Jurnal Fisika dan Aplikasinya, 2022)
Research has been carried out to map and identify the potential for soil corrosion for the planning of cathodic gas pipeline protection systems. The research location is located in Cimanggis - Bitung, West Java, which is located at coordinates 6o19'00 "- 6o28'00" South Latitude and 106o43'00 "- 106o 55'30" East Longitude. Measurement of soil resistivity using the Wenner method that refers to ASTM G37, with variations in the distance of 0,75m, 1,50m, 2,50m and 6,00m with the number of measuring points as many as 185 points. Based on the results of data processing and soil resistivity interpretation seen that there are several locations that have low to extreme corrosion levels. Therefore, for these locations, technical planning and calculation for the protection of the pipeline to be installed is necessary.